ANALISIS PENGARUH INDEKS PEMBANGUNAN MANUSIA (IPM), PERTUMBUHAN EKONOMI, DAN PENGANGGURAN TERHADAP KEMISKINAN DI INDONESIA (Equilibrium: Jurnal Ekonomi Syariah, 2018)
Poverty is a problem in development that must be reduced because it can cause several social problems. Islam considers that poverty can endanger the soul and faith, so that it is considered close to kufr. Based on the existing theories and some researches that have been done, the poverty problem is generally related to some factors such as quality of human resources, unemployment, and economic growth. This study aims to determine the influence of human development index (HDI), unemployment rate, and economic growth directly to the rate of poverty. In addition, it aims to know the indirect effects of HDI and economic growth through unemployment in influencing the rate of poverty. This study belongs to quantitative research using secondary data from BPS with panel data are time series data from 2013-2017 and cross section data are from 33 provinces in Indonesia. The data processing applies path analysis using WarpPLS 5.0 software. The results of this study indicate that the HDI affect directly and negatively to the rate of poverty with path coefficient of the -0.71. Economic growth has no significant effect on poverty reduction with probability 0.23. Then, it shows that unemployment has positive effect on poverty rate with path coefficient of 0.14 and have significant influence with probability 0.0035. This study also shows that unemployment can mediate HDI and poverty. In addition, unemployment can also mediate economic growth and poverty.